Serine enrichment in tumors promotes regulatory T cell accumulation through sphinganine-mediated regulation of c-Fos - Ma, Sicong; Sandhoff, Roger; Luo, Xiu; Shang, Fuwei; Shi, Qiaozhen; Li, Zhaolong; Wu, Jingxia; Ming, Yanan; Schwarz, Frank; Madi, Alaa; Weisshaar, Nina; Mieg, Alessa; et al. (Science immunology, 2024)
CD4+ regulatory T (Treg) cells accumulate in the tumor microenvironment (TME) and suppress the immune system. Whether and how metabolite availability in the TME influences Treg cell differentiation is not understood. Here, we measured 630 metabolites in the TME and found that serine and palmitic acid, substrates required for the synthesis of sphingolipids, were enriched. A serine-free diet or a deficiency in Sptlc2, the rate-limiting enzyme catalyzing sphingolipid synthesis, suppressed Treg cell accumulation and inhibited tumor growth. Sphinganine, an intermediate metabolite in sphingolipid synthesis, physically interacted with the transcription factor c-Fos. Sphinganine c-Fos interactions enhanced the genome-wide recruitment of c-Fos to regions near the transcription start sites of target genes including Pdcd1 (encoding PD-1), which promoted Pdcd1 transcription and increased inducible Treg cell differentiation in vitro in a PD-1-dependent manner. Thus, Sptlc2-mediated sphingolipid synthesis translates the extracellular information of metabolite availability into nuclear signals for Treg cell differentiation and limits antitumor immunity.